Developing reliable floating solar systems on seas: a review - Huang, Luofeng; Elzaabalawy, Hashim; Sarhaan, Mohamed; Sherif, Ahmed; Ding, Haoyu; Ou, Binjian; Yang, Danlei; Cerik, Burak Can (Elsevier, 2025)
Solar PhotoVoltaic (PV), as a clean and affordable energy solution, has become ubiquitous around the world. In order to install enough PV coverage to meet the demand of global climate action, there has been a growing research interest in deploying solar panels on abundant sea space. However, the harsh marine environment is holding stakeholders back with safety concerns. There is a necessity to ensure the reliability of FPV on seas. To facilitate research in this area, the present review scans all Floating PV (FPV) literature related to the ocean, with a focus on reliability and risk mitigation. It starts by presenting contemporary and potentially future FPV designs for seas, inventorying both mechanical and electrical components. Accordingly, possible risks in the system are discussed with the associate mitigations suggested. Subsequently, a series of protective approaches to assess offshore wind and wave loads on FPV are introduced. This is followed by a structural integrity review for the system’s fatigue and ultimate strength, accompanied by anti-corrosion, anti-biofouling, and robust mooring concerns. Finally, essential research gaps are identified, including the modelling of numerous floating bodies on seas, mooring methodology for enormous FPV coverage, the interactions between FPV and the surrounding sea environments, and remote sensing and digital twins of the system for optimal energy efficiency and structural health. Overall, this work provides comprehensive insights into essential considerations of FPV on seas, supporting sustainable developments and long-term cost reductions in this sector.
Keywords: Civil Engineering; 4012 Fluid mechanics and thermal engineering; 4015 Maritime engineering; Floating solar; Seas; Mechanical; Electrical; Risks; System integrity